Role of Gene Length in Control of Human Gene Expression: Chromosome-Specific and Tissue-Specific Effects - Jay C. Brown (International Journal of Genomics)
This study was carried out to pursue the observation that the level of gene expression is affected by gene length in the human genome. As transcription is a time-dependent process, it is expected that gene expression will be inversely related to gene length, and this is found to be the case. Here, I describe the results of studies performed to test whether the gene length/gene expression linkage is affected by two factors, the chromosome where the gene is located and the tissue where it is expressed. Studies were performed with a database of 3538 human genes that were divided into short, midlength, and long groups. Chromosome groups were then compared in the expression level of genes with the same length. A similar analysis was performed with 19 human tissues. Tissue-specific groups were compared in the expression level of genes with the same length. Both chromosome and tissue studies revealed new information about the role of gene length in control of gene expression. Chromosome studies led to the identification of two chromosome populations that differ in the expression level of short genes. A high level of expression was observed in chromosomes 2-10, 12-15, and 18 and a low level in 1, 11, 16-17, 19-20, 22, and 24. Studies with tissue-specific genes led to the identification of two tissues, brain and liver, which differ in the expression level of short genes. The results are interpreted to support the view that the level of a gene’s expression can be affected by the chromosome and the tissue where the gene is transcribed.